Exploring Students' Perceptions of Blended Learning in Basic Education: A Qualitative Study - Cara Frances K. Abendan; Jason Isaac III A. Rabi; Jhonrey C. Uy; Peras (Academia One Publishing, 2023)
Blended learning is an innovative approach that combines traditional face-to-face instruction with online learning activities. It has gained popularity in basic education, particularly in senior high school levels. This qualitative study aimed to explore students' perceptions of blended learning in basic education. The study involved senior high school students from a public school in the Philippines. The findings of the study revealed that students had a basic understanding of blended learning, but they perceived it differently. Some students viewed it positively, while others had reservations about its effectiveness. The study also showed that students faced various challenges in blended learning, such as technical difficulties, lack of interaction with teachers, and difficulty in managing time. Furthermore, the study identified several factors that influence students' perceptions of blended learning. These include students' prior experiences with technology, the quality of instructional materials, and the level of teacher support. The study provides insights into students' perceptions of blended learning, which can inform the development of effective blended learning programs in basic education. The findings of the study can also guide educators in addressing the challenges that students encounter in blended learning
Keywords: blended learning; basic education; senior high school; students